An open randomized trial of artemether versus quinine in the treatment of cerebral malaria in African children. - Murphy, S; English, M; Waruiru, C; Mwangi, I; Amukoye, E; Crawley, J; Newton, C; Winstanley, P; Peshu, N; Marsh, K (1996)
We have compared the efficacy of artemether versus quinine as treatment for cerebral malaria in children in an open randomized clinical trial in Kenya. Children admitted to hospital with coma and Plasmodium falciparum parasitaemia were treated with either intramuscular artemether (3.2 mg/kg loading dose followed by 1.6 mg/kg daily) or intravenous quinine (20 mg/kg loading dose followed by 10 mg/kg every 8 h). Both drugs were well tolerated and no significant adverse effect was observed. Parasite clearance times (50% and 90%) were shorter in patients treated with artemether (median times [h], with interquartile ranges in brackets, were: 50%, 7.3 [4.2-12.4] vs. 15.5 [9-22]; 90%, 16.9 [13.2-25] vs. 28.5 [22-35]; P < 0.0001). The total mortality in 160 children with cerebral malaria was 16.25%, with no overall significant difference between the 2 treatment groups. In a subgroup of children with respiratory distress, mortality was higher in those treated with artemether (43.7% vs. 11.1%, P < 0.05). The frequency of neurological sequelae and clinical recovery times were similar in both treatment groups. We conclude that there would currently be no advantage in replacing quinine with artemether for the treatment of cerebral malaria in African children.